Drosophila at the intersection of infection, inflammation, and cancer - Bangi, Erdem (Frontiers in Cellular and Infection Microbiology, 2013)
Recent studies show that both cellular and humoral aspects of innate immunity play important roles during tumor progression. These interactions have traditionally been explored in vertebrate model systems. In recent years, Drosophila has emerged as a genetically tractable model system for studying key aspects of tumorigenesis including proliferation, invasion and metastasis. The absence of adaptive immunity in Drosophila provides a unique opportunity to study the interactions between innate immune system and cancer in different genetic contexts. In this review, I discuss recent advances made by using Drosophila models of cancer to study the role of innate immune pathways Toll/Imd, JNK and JAK-STAT, microbial infection and inflammation during tumor progression.